Nursing Students' Migration Intentions: A Comparative Study of Türkiye and The Philippines - Cemre Karatiken; Gulcan Bagcivan; Ruhat Tilki; Ayise Karadag (Nursing and Health Sciences Journal (NHSJ), 2024)
This study aims to determine the migration intention of nursing students and the factors affecting it in Türkiye and the Philippines. A total of 284 nursing students were included in this descriptive study. The "Personal Data Form" was used for data collection, which included questions about the participants' sociodemographic characteristics and their intention to migrate. 87% of the students stated that they intend to migrate abroad. The three most frequently indicated reasons for migration are inadequate nursing salaries (73.6%), insufficient increase in salary relative to inflation in the country (60.6%), and unequal wage distribution (55.3%). Nursing migration will inevitably increase over time and create problems in health service delivery among many countries. Nurses will tend to migrate to countries with better conditions, especially with the difficult working conditions brought on by the COVID-19 pandemic. As the nurse migration continues, the increasing shortages in the number of nurses in the emigrant countries cause nurses to work in heavier conditions and longer shifts, preventing the provision of quality and adequate health services. To reduce nursing migration, policymakers must produce solutions by considering the reasons that lead to migration.